2021
DOI: 10.32819/021019
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of post-emergence (“insurance”) herbicides in soybean crops of the Northern Steppe of Ukraine

Abstract: Loss of soybean yields from weeds can reach 30–50%. Chemical methods of their control are of primary importance for obtaining the maximum grain yield. The critical period for weed control is stage from the first to third true leaf of the crop. The most active growth of unwanted vegetation in soybean crops is observed in the spring-summer period. And if during this period you can mainly suppress weeds, then in the future the crops will be relatively clean. In years when there is a sharp lack of moisture at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
4
0
3
Order By: Relevance
“…However, disturbance is also known to increase the invasibility of communities. Disturbance therefore poses an important problem for conservation management (Hobbs & Huenneke, 1992;Tkalich et al, 2021;Yorkina et al, 2021). Our study confirmed that up to 90% of the mapped sites represent significantly disturbed habitats with a high degree of anthropogenic influence.…”
Section: Discussionsupporting
confidence: 77%
“…However, disturbance is also known to increase the invasibility of communities. Disturbance therefore poses an important problem for conservation management (Hobbs & Huenneke, 1992;Tkalich et al, 2021;Yorkina et al, 2021). Our study confirmed that up to 90% of the mapped sites represent significantly disturbed habitats with a high degree of anthropogenic influence.…”
Section: Discussionsupporting
confidence: 77%
“…Endogenous phytohormones take part in the management of physiological and biochemical processes at different levels of organization of the plant organism, the regulation of morphogenesis and plant production process. Changes in the rate of growth processes under the action of exogenous growth regulators and their synthetic analogues and modifiers, in particular gibberellin-like compounds and their inhibitors, are due to changes in the balance of endogenous phytohormones (Rademacher, 2016;Khalloufi et al, 2017;Song et al, 2019;Tkalich et al, 2021;Tsyliuryk et al, 2021). Therefore, the effect of gibberellins and anti-gibberellin preparations on the growth, development and productivity of cultivated plants requires further study (Jabir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Everything aforesaid has led to most formely common species of plants and animals becoming rare or endangered and now included in the Red Book of Ukraine and the Red Book of Dnipropetrovsk Region. The greatest threat for the biodiversity in the Region is posed by destruction of certain types of landscapes (virgin steppe areas, bairak forests, meadow ecosystems); invasion of the natural ecosystems by alien and genetically-modified organisms; urbanization, uncontrolled use of land resources; industrial impact (mining fossil fuels, impact of energetics, transport, and other kinds of industrial activity); agricultural impact (plant agriculture, livestock farming); impact of forestry and hunting; impact of water economics (Kunakh et al, 2020;Fedyushko & Babchenko, 2021;Tkalich et al, 2021;Yorkina et al, 2021).…”
Section: Ecological Situation In Dnipropetrovsk Regionmentioning
confidence: 99%